Peptides as surface coatings of nanoparticles that penetrate human cystic fibrosis sputum and uniformly distribute in vivo following pulmonary delivery - Leal, Jasmim (J Control Release, 2020)
Therapeutic delivery of drug and gene delivery systems have to traverse multiple biological barriers to achieve efficacy. Mucosal administration, such as pulmonary delivery in cystic fibrosis (CF) disease, remains a significant challenge due to concentrated viscoelastic mucus, which prevents drugs and particles from penetrating the mucus barrier. To address this problem, we used combinatorial peptide-presenting phage libraries and next-generation sequencing (NGS) to identify hydrophilic, net-neutral charged peptide coatings that enable penetration of human CF mucus ex vivo with ~600-fold better penetration than control, improve uptake into lung epithelial cells compared to uncoated or PEGylated-nanoparticles, and exhibit enhanced uniform distribution and retention in the mouse lung airways. These peptide coatings address multiple delivery barriers and effectively serve as excellent alternatives to standard PEG surface chemistries to achieve mucus penetration and address some of the challenges encountered using these chemistries. This biomolecule-based strategy can address multiple delivery barriers and hold promise to advance efficacy of therapeutics for diseases like CF.